Verbalna komunikacija učiteljev v povezavi z učno uspešnostjo dijakov - Seničar, Eva (Šport (Ljubljana), 2021)
Communication is a means of transmitting information that takes place in everyday life. It is extremely important because it provides interaction between people and is a form of human social activity. As a result, communication is also important in school. The most common is verbal communication, which is also accompanies by nonverbal. It is rare for communication to be interrupted during class, as it also takes place when students and the teacher are silent. In the research, we wanted to find out how important is the verbal communication of teachers in connection with the learning performance of students in individual subjects in high school. Our goals were to determine what is the verbal communication of teachers in high school, whether it is related to the learning performance of students, and to determine whether there are differences between individual teachers of different subjects and between different years of students. Students of all four years and mixed by gender were included. We found that there is a statistically significant association between teacher verbal communication and students’ learning performance, as positive aspects of verbal communication positively affect students’ learning performance. Differences in the assessment of verbal communication of individual teachers were shown between individual years and also by gender. The best assessment of verbal communication is with physical education teachers, where is also the highest learning success.
Keywords: communication in school; komuniciranje; komunikacija v šoli; learning performance; sport; students; šport; teachers; učenci; učitelji; učna uspešnost; verbal communication; verbalne komunikacije